(untitled) (Research, Society and Development, 2020)
The debate between Science and Religion has marked the last centuries, with current implications for the teaching of Science. In This context, the general objective of this study is to know the influence of the educational environment in the face of evolutionary thinking about the expression of belief in God and religiosity among middle-level students of a school in the interior of Brazil. Semi-structured interviews Were conducted with students from the 3rd year of High School in a State college located in the city of Alto Alegre do Maranhão. Na Research was used semi-structured interview characterizing The socio-demographic profile of the participants, based on the didactic book for discussing and conducting a seminar, therefore applying a post-survey questionnaire. The results indicate that the school contributes and fosters discussions on current issues, of Community interest or related to social problems.